2019
DOI: 10.1103/physrevfluids.4.053901
|View full text |Cite
|
Sign up to set email alerts
|

Second-order sensitivity in the cylinder wake: Optimal spanwise-periodic wall actuation and wall deformation

Abstract: Two-dimensional (2D) flows can be controlled efficiently using spanwise "waviness", i.e. a control (e.g. wall blowing/suction or wall deformation) that is periodic in the spanwise direction. This study tackles the global linear stability of 2D flows subject to small-amplitude 3D spanwise-periodic control. Building on previous work for parallel flows [1], an adjoint method is proposed for computing the second-order sensitivity of eigenvalues. Since such control has indeed a zero net first-order (linear) effect,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The same observation had been reported before from studies of instability control in plane two-dimensional flows via spanwise-periodic base flow modifications (Hwang & Choi 2006; Tammisola et al. 2014; Boujo, Fani & Gallaire 2019). If, however, in the present configuration, rolls and streaks in jets cause first-order variations in the instability eigenvalues, then a sensitivity analysis will allow us to identify roll shapes that optimally destabilise linear eigenmodes.…”
Section: Linear Stability Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…The same observation had been reported before from studies of instability control in plane two-dimensional flows via spanwise-periodic base flow modifications (Hwang & Choi 2006; Tammisola et al. 2014; Boujo, Fani & Gallaire 2019). If, however, in the present configuration, rolls and streaks in jets cause first-order variations in the instability eigenvalues, then a sensitivity analysis will allow us to identify roll shapes that optimally destabilise linear eigenmodes.…”
Section: Linear Stability Analysissupporting
confidence: 80%
“…In the context of streaks in plane shear layers, Marant & Cossu (2018) demonstrated that this analysis needs to be expanded to second order, if one wishes to correctly retrieve the quadratic dependency of eigenmodes on streak amplitude. The same observation had been reported before from studies of instability control in plane two-dimensional flows via spanwise-periodic base flow modifications (Hwang & Choi 2006;Tammisola et al 2014;Boujo, Fani & Gallaire 2019). If, however, in the present configuration, rolls and streaks in jets cause first-order variations in the instability eigenvalues, then a sensitivity analysis will allow us to identify roll shapes that optimally destabilise linear eigenmodes.…”
Section: Linear Sensitivity Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…The separation angle of the flow was not investigated. Very recently, the optimum spanwise-varying suction/blowing control of a 3D circular cylinder in 2D flow was determined using eigenmode analysis by Boujo et al 21 Due to the nature of this method, though, it can only be used to optimise for stabilisation or frequency modification which does not necessarily coincide with minimised drag or the elimination of separation. All of these studies were performed by numerical methods; non-uniform suction has not been explored substantially by physical experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…On the stabilization of three-dimensional flows, Tammissola [20] and Tammissola et al [21] used a second-order perturbation analysis on the optimization of spanwise-periodic shaping and actuation of a cylindrical body to stabilize the vortex shedding. Boujo et al [22,23] developed an adjoint method to extract the second-order sensitivity of the leading eigenvalues, predicting optimal wall actuation and wall deformation on spanwise-periodic flows, and reducing the complexity of a three-dimensional problem to a two-dimensional analysis. More recently, Brewster and Juniper [24] employed a continuous adjoint approach to obtain the shape gradients of the eigenvalues related to the cylinder wake first instability, and analyze the effects of the local deformations on the flow instability.…”
Section: Introductionmentioning
confidence: 99%